Let Us Kiss and Part; or, A Shattered Tie - Miller, Alex. McVeigh, Mrs., 1850-1937 (Salt Lake City, UT : Project Gutenberg, 2021)
"Let Us Kiss and Part; or, A Shattered Tie" by Mrs. Alex. McVeigh Miller is a romance novel written in the late 19th century. The story revolves around Leon and Verna Dalrymple, a young couple whose marriage, clouded by pride and the harsh realities of poverty, leads to their bitter separation. Their tumultuous relationship serves as the backdrop for the development of a deeper narrative, which ultimately centers around their daughter, Jessie, as she navigates a world filled with love, loss, and the search for her true identity. At the start of the story, the couple is depicted on the verge of a heartbreaking separation due to escalating tensions fueled by their dire financial situation. Verna, driven by desperation, threatens to return to her wealthy family and seek a divorce, leading to a pivotal moment where both characters feel the weight of their unresolved feelings. The narrative then shifts sixteen years later, introducing Jessie, who is left to fend for herself and her younger brothers after their parents' tragic choices. The opening sections create a rich context of love's complexities, the impacts of societal status, and the themes of longing and familial obligation, setting the stage for Jessie$1 (Bs future encounters and the entanglements that will define her life. (This is an automatically generated summary.)s
Release date is 2021-11-19
Demian Katz, Craig Kirkwood, and the Online Distributed Proofreading Team at https://www.pgdp.net (Images courtesy of the Digital Library@Villanova University.)
Keywords: Fiction